GNSS spoofing in conflict zones disrupts wildlife tracking and hampers research and conservation efforts - Jiguet, Frédéric; Mayrose, Asaf; Piha, Markus; Efrat, Ron; Seimola, Tuomas; Sapir, Nir; Timonen, Sami; Wasserlauf, Yohay; Besnard, Aurélien; Bocher, Pierrick; Kölzsch, Andrea; Lehikoinen, Aleksi; et al. (Nature communications, 2025)
In war and conflict zones, the jamming of Global Navigation Satellite System (GNNS) signals by military forces disrupts the tracking of tagged animals, and has increased in frequency following the recent escalation of conflicts in Eastern Europe and the Middle East. Such disruption to data collection strongly hampers research into the protection and conservation of endangered animals.